Metastasis-Associated in Colon Cancer-1 Associates With Poor Prognosis and Promotes Cell Invasion and Angiogenesis in Human Cervical Cancer. Issue 8 (October 2015) - Zhou, Xiang; Xu, Chang-Juan; Wang, Jun-Xian; Dai, Ting; Ye, Ya-Ping; Cui, Yan-Mei; Liao, Wen-Ting; Wu, Xin-Lin; Ou, Jian-Ping
<x xml:space="preserve">Abstract</x> Objective The aim of this study is to investigate the clinicopathologic significance and potential role of metastasis-associated in colon cancer-1 (MACC1) in the progression of cervical cancer. Methods MACC1 expression was examined in cervical cancer cell lines, 6 matched cervical cancer tissues, and adjacent noncancerous tissues using Western blotting and real-time reverse transcriptase polymerase chain reaction. MACC1 protein expression and localization were determined in 181 paraffin-embedded archived cervical cancer samples using immunohistochemistry. Statistical analyses were applied to evaluate the clinicopathologic significance. The effects of MACC1 on cell migration, invasion, and angiogenesis were examined using migration assay, wound healing assay, 3-dimensional morphogenesis assay, and chicken chorioallantoic membrane assay. Western blotting was performed to examine the impact of MACC1 on the Akt and nuclear factor κB signaling pathways. Results Both protein and messenger RNA levels of MACC1 was up-regulated in cervical cancer cell lines and cervical cancer tissues, as compared with normal tissues. High MACC1 expression was detected in 96 (53%) of 181 of the cervical cancer tissues. In addition, high MACC1 expression correlated significantly with aggressiveness of cervical cancer, including International Federation of Gynecology and Obstetric stage (P = 0.001), pelvic lymph node metastasis (P = 0.004), recurrence (P = 0.037), and poor survival (P = 0.001). Moreover, enforced expression of MACC1 in cervical cancer cell lines significantly enhanced cell migration, invasion, and angiogenesis. Conversely, knockdown of MACC1 caused an inhibition of cell migration, invasion, and angiogenesis. Up-regulation of MACC1 increased, but knockdown of MACC1 decreased the expression of matrix metalloproteinase-2 and matrix metalloproteinase-9. Furthermore, enforced expression of MACC1 could enhance, but knockdown of MACC1 could reduce AKT and nuclear factor κB pathway activity. Conclusions Our findings suggest that MACC1 protein, as a valuable marker of cervical cancer prognosis, plays an important role in the progression of human cervical cancer cells.